Internet Social Networking Risks at Children - Kovačević-Lepojević, Marina; Žunić-Pavlović, Vesna (Zbornik Instituta za kriminološka i sociološka istraživanja, 2011)
Children around the world have almost daily access to social networking sites in order to achieve interpersonal interactions with peers. Social networking can contribute to the development of creativity, self-efficacy, various academic achievements, self-esteem, tolerance for diversity and social skills of children, but they are also at risk of abuse and violence. The first objective of this study was to analyze the results of contemporary research on children's risks of social networking on the Internet. Featured are discussed and the most important indicators of risk jeopardizing the safety of children, as well as profiles of over 100 friends, contact with strangers, leaving personal information on profiles, poor digital literacy of children and parents, excessive use of the Internet, previous victimization, and more. The second objective of this paper is the presentation of successful procedures for reducing risk and strengthening the resilience of children in social networking that can take the owners of these sites, parents, teachers and other subjects.